Family medicine in Tanzania: Seize the moment - Riaz Ratanzi; Bernhard M. Gaede (AOSIS, 2020)
In the context of addressing the pressing health needs for the global population, the World Health Organization has repeatedly called for universal health coverage (UHC) to be prioritised by its member countries. This is to be achieved through a high-quality primary health care (PHC) approach that provides comprehensive and integrated generalist care as close to where people live as well as links the clinical care to health promotion and disease prevention. In this paper, we argue for the introduction of family medicines as a critical player in the healthcare system of Tanzania to strengthen the strategies towards UHC. The paper reviews how PHC is understood, the context of family medicine in sub-Saharan Africa and makes a case for how family medicine can assist in addressing the current burden of disease in Tanzania.